Qualidade microbiológica e físico-química de Queijo Minas artesanal da Canastra durante a maturação em estação chuvosa - Ranier Chaves Figueiredo (2022)
Minas artisanal cheese results from cultural heritage of Portuguese colonists native to the Azores Archipelago. The region of Serra da Canastra-MG was notable for the production and commercialization of this artisanal cheese that is currently protected by a Geographical Indication. The objective of this work was microbiological and physicochemical characterization of Minas artisanal cheese made in the region of Serra da Canastra, Minas Gerais, during 22 days of ripening in legalized farms, or in the qualification phase of sanitary legalisation. The physicochemical and microbiological quality of 96 cheeses, 16 samples of raw milk, 16 samples of pingo and 16 samples of water used in the cheese farms of 16 properties located in the Serra da Canastra-MG region were analyzed. Were detected reductions (p0.05) in the counts of total coliforms, thermotolerant coliforms and coagulase positive Staphylococcus in cheeses during the 22 days of ripening. The enumeration of lactic acid bacteria (LAB) increased up to nine days of ripening, with a decrease from nine to 22 days of ripening. The proteomic identification of the different morphotypes of colonies selected from the BAL enumeration survey indicated a predominance of lactococcus lactis and Streptococcus spp. at the beginning of ripening. The identification of bacteria of the genus Staphylococcus spp. were frequent up to nine days of maturation, not being detected after 14 days of maturation. Bacillus cereus was detected in a cheese of five and a cheese of 14 days of ripening. There was no detection of Listeria monocytogenes in the water, raw milk, pingo and cheese samples studied. There was detection of Salmonella spp. in a raw milk sample, one cheese from one day of ripening and a five-day ripening cheese. However, the colonies were firstly identified as Salmonella spp. using classical methods of cultivation, but when they were submitted for proteomic identification, it was observed that none of them belonged to the genus Salmonella spp. 14 days of ripening was able to reduce the microbial counts in accordance with the parameters established in legislation, with the exception of cases where there is an incidence of recontamination. Maturation also influenced the average percentage of moisture, total dry stratum, fat and protein in the cheeses. The results of this research allowed the publication of the regulation IMA n°2051 of April 7, 20221, defining the period of 14 days of ripening as the minimum necessary for the production of artisanal Minas cheese from the Serra da Canastra region.